2013
DOI: 10.1177/1934578x1300800619
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical, Antimicrobial and Antiplasmodial Investigations of Terminalia brownii

Abstract: Phytochemical investigation of the ethyl acetate-soluble fraction of stem bark extract of an African medicinal plant Terminalia brownii led to the isolation of a new oleanane-type triterpenoid, along with seven known triterpenoids, seven ellagic acid derivatives, and 3-O-β-D-glucopyranosyl-β-sitosterol. The new compound was identified using spectroscopic methods, notably 1D- and 2D NMR, as 3β,24-O-ethylidenyl-2α,19α-dihydroxyolean-12-en-28-oic acid. The isolated compounds were evaluated for their antimicrobial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…11 Previous studies on the plant reported the antimicrobial activity of its extracts and fractions. [10][11][12] Terminalia brownii is one of the most In our study, the primary complaint of patients was intense pruritus on the legs. Some of the patients had lichenification of the skin with lichen simplex chronicus lesions on their legs as a result of excessive scratching.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…11 Previous studies on the plant reported the antimicrobial activity of its extracts and fractions. [10][11][12] Terminalia brownii is one of the most In our study, the primary complaint of patients was intense pruritus on the legs. Some of the patients had lichenification of the skin with lichen simplex chronicus lesions on their legs as a result of excessive scratching.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, Terminalia brownii has been found to have antioxidant activities and hepatoprotective properties . Previous studies on the plant reported the antimicrobial activity of its extracts and fractions . Terminalia brownii is one of the most important plants in treatment of tick‐borne diseases and is known to have antibacterial activity aganist Porphyromonas gingivalis …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, the antibacterial activity of the 5% water-methanol crude extract of T. brownii against F. columnare was attributed to the two isolated compounds 1 and 2 present in the extract. A previous study [9] investigating antimicrobial activities of stem bark extracts of T. brownii also isolated and identified 2 as possessing antibacterial activity against the Gram-negative bacterium Pseudomonas aeruginosa, with an IC 50 of 8.8 µg/mL and thereby indicating greater susceptibility to 2 than F. columnare, with a 24 h IC 50 = 31±1 µg/mL (Table 3). Before conducting efficacy/challenge studies, further evaluation of the potential toxicity of the active compounds towards non-target organisms (e.g., channel catfish) will need to be determined.…”
mentioning
confidence: 93%